COORDINATING SECTIONS OF COURSES IN ELEMENTARY ACCOUNTING. - Van Voorhis, Robert H. (The Accounting Review, 1955)
The article focuses on coordinating sections of courses in elementary accounting. With college enrollments on the increase, many schools are having to offer more sections of elementary accounting courses. As the number of sections of any course increases, problems of planning and coordination are likely to arise or to become more acute. Different solutions to these problems have been attempted, with varying success. At the University of Alabama, Birmingham, Alabama, a somewhat unusual method of coordination has been developed for the second semester of the elementary accounting course. Its successful operation over the past three years suggests that others might find it beneficial in their schools. One difficulty, where seven instructors are teaching sections of the same course simultaneously, lies in keeping the pace of the work somewhat uniform. Some schools attack this problem by having a weekly lecture for the entire group, followed by discussion and perhaps laboratory periods in smaller sections. Many teachers feel, however, that the lecture to the large group is almost a complete waste of time, and refuse to adopt this expedient.